2005
DOI: 10.1016/j.limno.2005.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Long-term changes in cladoceran assemblages in the Danube floodplain area (Slovak–Hungarian stretch)

Abstract: In this paper, the distribution of Cladocera species in the different sampling sites: the main channel/old river bed, parapotamal type side arms and plesiopotamal side arms, is described. The structure of cladoceran assemblages in the by-passed Danube section and in the adjacent floodplain water bodies has changed since the Gabcˇı´kovo hydropower plant was put into operation. Great changes have been observed in the previous parapotamal side arm situated between river km 1840 and 1820, artificially fed with wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 5 publications
2
12
0
Order By: Relevance
“…It seems that this situation resulted from the rich macrovegetation that covered the littoral zone, allowing an increase in the number of macrophyte-associated species. Similar changes in cladoceran assemblages were reported by Illyova & Nemethova (2005) from the Danube floodplain area. An increase in macrophyte abundance has a large impact on cladoceran communities (Sweetman et al, 2010); it supports an increase in phytophilous cladocerans.…”
Section: Discussionsupporting
confidence: 85%
“…It seems that this situation resulted from the rich macrovegetation that covered the littoral zone, allowing an increase in the number of macrophyte-associated species. Similar changes in cladoceran assemblages were reported by Illyova & Nemethova (2005) from the Danube floodplain area. An increase in macrophyte abundance has a large impact on cladoceran communities (Sweetman et al, 2010); it supports an increase in phytophilous cladocerans.…”
Section: Discussionsupporting
confidence: 85%
“…The number of cladoceran (34) and copepod (16) species is relatively high and corresponds with other Danubian arms (Gulyás 1994;Bothár & Ráth 1994;Illyová & Némethová 2005). The number of cladoceran species found in the Rusovecké rameno arm represents as much as a half (54%) of all the species recorded in a (15 years) long-term monitoring of cladoceran assemblages in the Danube floodplain area (Illyová & Némethová 2005).…”
Section: Discussionmentioning
confidence: 69%
“…The number of cladoceran species found in the Rusovecké rameno arm represents as much as a half (54%) of all the species recorded in a (15 years) long-term monitoring of cladoceran assemblages in the Danube floodplain area (Illyová & Némethová 2005). Similarly, the number of copepod species in the arm is a half of the number of species (30) recorded in monitoring of the Danube river-basin waters by Vranovský (1997).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Present study confirmed the expansion of this species. In Hungary, Pleuroxus denticulatus has only been reported from the Szigetköz region (Gulyás & Forró 1999), but has been depected as an invador in the Slovakian floodplain area (Illyová & Némethová 2005). The dominance of the smallbodied cladoceran Bosmina longirostris, nauplii and copepodites are in keeping with the findings of Gulyás (1994Gulyás ( , 1995 and Bothár (1978Bothár ( , 1994 but the relative contribution of copepodites is rather low in this study (it is almost equal to those of adult copepods), nevertheless, Bothár (1978) got to similar results.…”
Section: Discussionmentioning
confidence: 99%